The Transformation of the Independent Curriculum: Integrating 21st Century Skills and Islamic Educational Values in Facing the Era of Disruption - Lutfi Nurwahid; Liah Tarliah (Islamic Journal of Education, 2025)
The era of volatility, uncertainty, complexity, and ambiguity (VUCA) demands a fundamental redefinition of educational paradigms. This study aims to critically analyze the implementation of the Kurikulum Merdeka (Independent Curriculum) as a strategic instrument in accelerating 21st-Century Skills (critical thinking, creativity, collaboration, and communication) and its intersection with the ontology of holistic Islamic education. Employing a qualitative descriptive-analytical approach and extensive literature review, this research dissects the epistemological shift in the classroom—from instructional pedagogy to cognitive autonomy. The findings indicate that the Independent Curriculum structurally succeeds in deconstructing learning authority through the integration of Project-Based Learning (PjBL) and instructional differentiation. This flexibility not only stimulates student agency in solving contextual problems but also resonates with the concept of ta'dib, integrating intellectual and spiritual intelligence to form the insan kamil (perfect human). Nevertheless, critical discourse reveals that the curriculum's effectiveness is still reduced by digital literacy disparities and the cultural resistance of educators in marginalized areas. This study concludes that the Independent Curriculum is an essential social engineering tool, yet it requires a continuous transformation of the educators' professional ecosystem to align with the demands of global citizenship.